2015
DOI: 10.7439/ijbr.v6i10.2555
|View full text |Cite
|
Sign up to set email alerts
|

Papillomavirus: Viral vectors in the gene therapy and new therapeutic targets

Abstract: Epitheliotropic and mucosotropic Papillomaviruses (PVs) constitute the Papillomaviridae family. There are 26 genera comprising levels of inter species genetic similarities by nucleotide sequence analysis of the L1 viral region, the generally most conserved region among papillomaviruses. There is an increasing consensus that the ideal vector for gene therapy should be completely based on chromosomal elements and behave as an independent functional unit after integration. The present paper is a short review abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…DNA-based vaccines, recombinant proteins, nanoparticles, synthetic peptides, viral and non-viral vectors may be novel therapeutic targets to HPV vaccination [7]. So, mRNA vaccines encoding tumor-associated antigens (TAA) as CEA (Carcinoembryonic Antigen), HER2/neu, MUC1 (Mucin 1), NY-ESO-1 associated colorectal and other adenocarcinomas, gastric cancer, colorectal cancer, epithelial cancers, esophageal cancer, respectively [5].…”
Section: Making Mrna Cancer Vaccines a Realitymentioning
confidence: 99%
“…DNA-based vaccines, recombinant proteins, nanoparticles, synthetic peptides, viral and non-viral vectors may be novel therapeutic targets to HPV vaccination [7]. So, mRNA vaccines encoding tumor-associated antigens (TAA) as CEA (Carcinoembryonic Antigen), HER2/neu, MUC1 (Mucin 1), NY-ESO-1 associated colorectal and other adenocarcinomas, gastric cancer, colorectal cancer, epithelial cancers, esophageal cancer, respectively [5].…”
Section: Making Mrna Cancer Vaccines a Realitymentioning
confidence: 99%
“…Experimental studies in mice and non-human primates showed strong immunogenicity and anti-tumor effects demonstrating messenger RNA-HPV therapeutic vaccine as prophylactic vaccine for HPV [8]. Therefore, another platforms DNA-based vaccines, recombinant proteins, nanoparticles, synthetic peptides, viral and non-viral vectors may be novel therapeutic targets and prophylactic HPV vaccination [12] (figure 1).…”
Section: Human Papillomavirus (Hpv)mentioning
confidence: 99%
“…The mucosal HPV types have been described in the Alpha papillomavirus genus that infects the anogenital epithelium. HPV is the most common sexually transmitted disease based on their oncogenic activity as high-risk (hr) type, low-risk type (lr) and type of undeterminedrisk depending upon the associated diseases [1][2][3].…”
Section: Introductionmentioning
confidence: 99%